Exploring the Relationship Between Education Levels and Non-Food Consumption in Indonesia - Ammar, Zul (Journal of Economics, Management, Accounting and Computer Applications, 2024)
This study examines the effect of education level on non-food consumption in Indonesia using quantitative analysis with secondary data from the March 2017 National Socioeconomic Survey (SUSENAS). The sample consists of 686,274 individuals aged 19 years and older, with variables including education level (independent variable) and non-food consumption expenditure (dependent variable). Simple linear regression analysis was employed, with data processed using STATA 17.  The results indicate that education level has a positive and significant effect on non-food consumption, as shown by the regression equation Y=322,493.7+800,907.8X+e. The regression coefficient of 800,907.8 implies that a one-level increase in education results in an 800,907.8-rupiah increase in non-food consumption. The p-value of <0.05 confirms the statistical significance of this relationship. However, the coefficient of determination (R²) of 0.0846 (8.46%) suggests that education explains only a small proportion of the variation in non-food consumption, with other factors, such as income, lifestyle, and demographics, likely playing a more dominant role. This study highlights the critical role of education in shaping consumption patterns and suggests policy implications, including improving access to quality education and addressing broader socioeconomic factors to enhance household welfare. Future research should incorporate additional variables and temporal dimensions to provide a more comprehensive understanding of the determinants of non-food consumption.